Macroeconomic dynamics and the IS puzzle - Raymond J. Hawkins; Chau N. Nguyen (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
The authors solve the IS puzzle for the G7 countries. They find that five of the G7 countries have the expected significant negative relationship between the output gap and the real-rate gap; the time series of the remaining two show material deviation from expected IS-curve behavior. The authors show that the observed time dependence of the interaction between the output and real-rate gaps can be represented in a parsimonious and practical manner using the theory of anelasticity that unifies partial-adjustment specifications of the IS curve.
http://dx.doi.org/10.7910/DVN/J161O0
Keywords: C22; E3; E32; E52; E61; 330; IS curve; Euler equation; inflation; anelasticity; monetary policy